Qorpo-Santo : pelos (des)caminhos da loucura no Brasil do Século XIX - Proença, Emanuele Luiz (2012)
The relation between Qorpo-Santo and madness became the subject of this research after the increased interest in the story of Qorpo-Santo, who like some other important artists, was considered insane and never received recognition for his literary compositions while he was alive. He was a teacher, writer and playwright who lived in the south of Brazil during the 19th century. And he produced work that the value for the theater and literature was discovered one hundred years later. He retired from teaching, and then his wife asked for the interdiction of mental insanity. However, the lawsuit was controversial and lasted for years; the judges required that Qorpo-Santo be examined by some doctors. He was also kept in a psychiatric hospital in Rio de Janeiro to be observed by the most important doctors of that time. All of these doctors, with just one exception, stated that Qorpo-Santo´s mental health was appropriate enough so that he could take care of his own life and his possessions. However, the judge´s final decision opposed medical opinion, and Qorpo-Santo lost these rights because he was definitively interdicted. So the objectives of this research are to discuss the conceptions of madness in Brazilian society in the second half of the 19th century and understand the manufacturing of madness in Qorpo-Santo considering the characteristics of health politics and the society of that time. First, it presents a review of other studies that talk about madness in Brazil in the nineteenth century and discusses the changes that occurred in understanding madness during this period. Also, it talks about the social practices that were aimed at mad persons. At the beginning of the 19th century, the mad persons usually walked freely into theirs communities, but then madness was considered a social problem and these people were brought to the institutions. Initially, they were brought to jails or charity institutions, later they went to psychiatric hospitals that were created in several Brazilian cities. Madness became a medical subject and, step by step, medicine achieved control over this issue, although this process happened differently in several regions. When the history of Qorpo-Santo and his texts were analyzed, it was observed that his experiences with madness had occured exactly in this moment of transition in conceptions of madness and the social practices directed at it. For example, disputes between different authorities were happening for the control over fools life. But while the different powers, like family, justice and medicine, were disputing amongst themselves, Qorpo-Santo fought alone to prove that he was not a crazy and that his rights had to be preserved. His writing was the most important tool in this fight, it can be understood as the precious story of a man who resisted the actions that were trying to overwhelm him.